GOVERNANCE THROUGH DIGITAL PROCUREMENT: AN EMPIRICAL STUDY OF MSME ENGAGEMENT ON GOVERNMENT E-MARKETPLACE (GEM) IN INDIA - Singh, Parneet; Vij, Sandeep (International Journal of Research -GRANTHAALAYAH, 2025)
The digitalization of public procurement has emerged as a critical governance reform in India, with the Government e-Marketplace (GeM) positioned as a central platform for enhancing transparency, efficiency, and inclusivity. This study examines the perceptions of Micro, Small, and Medium Enterprises (MSMEs regarding the E-procurement ecosystem in India, with a specific focus on their engagement with GeM. Anchored in the Diffusion of Innovation Theory and Good Governance Theory, the research explores how digital procurement platforms influence governance outcomes and operational experiences for MSMEs. Using a descriptive research design, primary data were collected through structured interviews from 115 MSME representatives across northern Indian states. Exploratory Factor Analysis (EFA) was employed to identify the underlying dimensions shaping MSMEs’ perceptions of GeM-enabled procurement. The results reveal seven key factors driving MSME adoption and engagement, with process simplification and transparency emerging as the most dominant dimension, followed by accountability and fairness, information reliability and administrative efficiency, accessibility and digital monitoring, information consistency and openness, transparency and monitoring, and competitive and professional procurement practices. The findings indicate that MSMEs perceive GeM not merely as a technological tool but as an institutional mechanism that reduces bureaucratic discretion, limits corruption, enhances fairness, and expands market access. While the platform significantly improves procurement transparency and efficiency, challenges related to digital readiness and capacity constraints remain, particularly for micro and small enterprises. The study contributes to the literature by empirically linking E-procurement adoption with good governance outcomes from the perspective of MSMEs—an underexplored stakeholder group in public procurement research. The paper offers targeted policy recommendations aimed at strengthening MSME participation through capacity building, platform refinement, and supportive governance interventions. Overall, the study underscores the transformative potential of GeM in fostering inclusive, transparent, and accountable public procurement, thereby supporting MSME competitiveness and sustainable economic development in India.